2005
DOI: 10.1177/1558925005os-1400105
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Fiber Nonwovens for Automotive Composites

Abstract: With increasing demand for automobiles in the global market, and a simultaneous pressure to address the issue of sustainability, there is continuing need for the incorporation of natural fiber based materials into automotives. The focus of recent research has been to produce compostable cotton fiberbased composites that can be safely disposed off after their intended use without polluting the atmosphere, in an environmentally safe manner. It is evident from studies being done jointly at the University of Tenne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…238 This was due to the better interface between fiber and matrix in cotton-based composites than wood-based composites. Nonwoven cotton-based composites were produced for automotive applications by Kamath et al 239 Cotton fibers are used in many value-added products and the demand for the fibers have increased which makes the fibers expensive. Recycled cotton blend fabrics were used as reinforcement to reduce the cost.…”
Section: Curaua Curaua (Ananas Erectifolius)mentioning
confidence: 99%
“…238 This was due to the better interface between fiber and matrix in cotton-based composites than wood-based composites. Nonwoven cotton-based composites were produced for automotive applications by Kamath et al 239 Cotton fibers are used in many value-added products and the demand for the fibers have increased which makes the fibers expensive. Recycled cotton blend fabrics were used as reinforcement to reduce the cost.…”
Section: Curaua Curaua (Ananas Erectifolius)mentioning
confidence: 99%
“…Cotton has properties comparable to these fibers and is a suitable candidate except for its relatively high price. Recent studies by Kamath et al [25][26] have shown that cotton when combined with flax or kenaf produces good molded products that have acceptable physical properties and acoustical insulation properties. In these studies waste or low quality cotton was used, and there was no need for bleaching, thus keeping the fiber cost low.…”
Section: Cotton Containing Nonwovens For Molded Productsmentioning
confidence: 98%
“…Cotton fibre has an excellent absorbency [65]. Cotton represents 46% of world production of natural and chemical fibres [66].…”
Section: Cottonmentioning
confidence: 99%
“…Summary of Natural Fibres characteristics. Adapted from[45,[58][59][60][61][62][63][64][65][66][67][68][69].…”
mentioning
confidence: 99%